MODEL PEMBUATAN KEPUTUSAN ENTREPRENEURSHIP CALON SARJANA EKONOMI - Dewi Pujian, Kun Ismawati (Prosiding Seminar Nasional, 2014)
Unemployment is one of the most crucial problem to be solved in Indonesia toward AEC 2015,the global economy market. Society enforce must be done by improving the understanding ofcandidate bachelor of economics about the importantance of entrepreneurship. This researchaimed to analyze entrepreneurship chance of candidate bachelor of economics in all colleges/universities in Eks Karesidenan Surakarta. This research done by digging the trigger factors of entrepreneurship. This research based on case study, with predictor variable and outcome variable. Intervalmeasurement scale used to measure predictor variable. Outcome variable measured with nominal scale in 2 categories of answer. Questionnaires have been spread to students in 2 stateuniversities and 20 private universities/ colleges in Eks Karesidenan Surakarta, and there were 217 questionaires could be processed. Answers of the questionnaires analysed with binary logistic regression. Result of this research showed that 3 (three) factors affectedentrepreneurship decision making of candidate for bachelor of economics were interesting inbusiness, family/friendsâs support, and working capital. The model was: PK = -14,757 +Â  0,340MinatÂ  +Â  0,405 DorongÂ  +Â  0,205 Modal.